High-performance magnesium-zirconium-carbon sliding plate brick suitable for calcium-treated steel and preparation and application thereof

By adopting the raw material composition and preparation process of high-performance magnesium zirconium carbon skateboard bricks, the problems of corrosion and cracks in existing skateboards when used on calcium-treated steels and other types of steels are solved, and the high corrosion resistance, oxidation resistance and thermal shock resistance of the skateboard are achieved, and the service life is extended.

CN119822856APending Publication Date: 2025-04-15ZHEJIANG ZILI HIGH TEMPERATURE TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510035484.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When used on calcium-treated steel, existing steel skateboards are prone to problems such as corrosion, cracks, thermal peeling, oxidative wool pulling and block drops around cast holes, resulting in a short service life.

Method used

High-performance magnesium-zirconium carbon skateboard bricks are used, and its raw material composition includes magnesium-zirconium sand, semi-stable zirconium oxide fine powder, metal Al powder, SiC powder, graphite powder, carbon black and high-temperature asphalt powder, etc., and is prepared through reduction and firing, asphalt impregnation and dry distillation, to improve the skateboard's erosion, oxidation and thermal shock resistance.

Benefits of technology

It significantly improves the skateboard's resistance to corrosion, oxidation and thermal shock resistance, extends its service life, and solves the problems of cracks, thermal peeling and other problems when used on a variety of steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235431570000021
    Figure BDA0005235431570000021
  • Figure BDA0005235431570000031
    Figure BDA0005235431570000031
  • Figure BDA0005235431570000081
    Figure BDA0005235431570000081
Patent Text Reader

Abstract

The invention discloses a high-performance magnesium-zirconium-carbon sliding plate brick suitable for calcium-treated steel as well as a preparation method and application of the high-performance magnesium-zirconium-carbon sliding plate brick. The high-performance magnesium-zirconium-carbon sliding plate brick is prepared from the following raw materials: magnesia particles, magnesia fine powder, magnesium-zirconium sand particles, semi-stable zirconium oxide fine powder, metal Al powder, elemental Si powder, SiC powder, graphite powder, carbon black, high-temperature asphalt powder, B4C powder and a binding agent. The preparation method comprises the following steps: mixing other raw materials except the magnesia particles, the magnesium-zirconium sand particles and the binding agent to obtain premixed powder; the preparation method comprises the following steps: mixing and grinding magnesia particles and magnesium-zirconium sand particles, then adding a binding agent for mixing and grinding, then adding premixed powder for mixing and grinding, ageing the obtained pug, then carrying out mechanical pressing molding, baking the molded sliding plate brick at 180-220 DEG C, then carrying out reductive firing at 700-1000 DEG C, impregnating with asphalt, and carrying out destructive distillation treatment at 500-600 DEG C to obtain the high-performance magnesium-zirconium-carbon sliding plate brick.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials for steelmaking, and in particular to a high-performance magnesium-zirconium-carbon slide brick suitable for calcium-treated steel, and a preparation method and application thereof. Background Art

[0002] Sliding gate refractory is a key component of the ladle and tundish continuous casting flow control system, which plays a role in controlling and regulating the flow of molten steel. The working conditions during its use are very harsh, mainly manifested in:

[0003] 1) Long-term contact with high-temperature molten steel, and being eroded and corroded by molten steel of different chemical compositions, such as the corrosion of calcium, manganese, oxygen and other elements in the molten steel of the grade steel;

[0004] 2) The temperature gradient during the steel pouring process reaches a sharp change of about 1000°C, causing huge thermal stress inside the material;

[0005] 3) The flow of molten steel is controlled by opening and closing the slide plate. There is a lot of wear between the plate surfaces during the back and forth movement of the slide plate;

[0006] 4) Both the ladle and the middle ladle slide are in a semi-open state for a long time during the steel pouring process, and the slide absorbs oxygen and is partially oxidized during the sliding process.

[0007] The above working conditions require that the skateboard has very excellent medium and high temperature strength, oxidation resistance, wear resistance, thermal shock stability, and resistance to molten steel erosion.

[0008] According to the usage experience of domestic and foreign steel mills, large and medium-sized ladles generally use aluminum-zirconium-carbon slide plates. If used on special steels, obvious erosion will occur, the service life will drop sharply, and even steel leakage accidents may occur. Some steel mills use slide plates inlaid with zirconium rings for use on special steels, but the processing technology is complicated and the manufacturing cost is high.

[0009] At present, the main problems existing in the use of aluminum zirconium carbon slide plates and inlaid zirconium ring slide plates on various steels are as follows:

[0010] (1) When aluminum-zirconium-carbon slide plates are used on various types of steel, such as calcium-treated steel, the calcium in the molten steel reacts with Al2O3 and SiO2 in the slide plates to form low-melting products. Some of them have horseshoe-shaped melting losses. In severe cases, the slide plates cannot be closed and steel leaks out. If used on high-oxygen steel, Al2O3-SiO2-FeO low-melting products appear, which cause severe erosion and even steel leaks out.

[0011] (2) When the slide plate inlaid with zirconium rings is used on a variety of steel, erosion may occur when the calcium content exceeds 40ppm. On the continuous casting platform, the slide plate will twitch frequently, which may easily cause problems such as zirconium plate peeling and steel clamping. When used on high-oxygen steel, if the oxygen content exceeds 100ppm, low-melting substances of the ZrO2-FeO series may appear, resulting in obvious melting loss. In addition, due to the large difference in thermal expansion coefficient between the zirconium ring and the mother plate, steel clamping may also occur during use.

[0012] Magnesium slide plates are also used on ladles in foreign countries. However, due to their large thermal expansion coefficient and poor thermal shock resistance, they are prone to cracks during use, and the proportion of continuous use is not high and their service life is short.

[0013] There is currently no record of mass use of magnesium-carbon skateboards in China. The main reason is that the thermal expansion coefficient is large, the thermal shock resistance is poor, and the skateboards are prone to cracks during use, making it difficult to extend their service life.

[0014] In recent years, scientific and technological workers have done a lot of research work on magnesium zirconium carbon skateboards. For example, invention patent document CN102584293A reported that magnesium zirconium sand, magnesium sand, spinel, Al powder, Si powder, carbon materials, etc. were introduced into the skateboard to improve the comprehensive performance of the sliding nozzle and extend the service life of the skateboard nozzle; the patent uses fused spinel raw materials, which has limited improvement in the corrosion resistance of calcium-treated steel; there is no material involving semi-stable zirconium oxide and other raw materials to improve the thermal shock resistance, and the ZrO2 mass percentage of the magnesium zirconium sand used is 4% to 6%, so the improvement of the thermal shock resistance of the skateboard is limited, and the improvement of the use cracks of the skateboard is also limited. Summary of the invention

[0015] The present invention provides a high-performance magnesium zirconium carbon slide brick suitable for calcium-treated steel, and a preparation method and application thereof. The present invention does not involve spinel raw materials. The high-performance magnesium zirconium carbon slide brick of the present invention has high volume stability, anti-stripping, anti-scouring performance, and high anti-corrosion performance after reduction sintering, asphalt impregnation, and dry distillation. It can be used in large, medium and small ladles of calcium-treated steel and other varieties of steel to greatly improve the service life.

[0016] [1] A high-performance magnesium zirconium carbon slide brick suitable for calcium treated steel, the raw material composition includes, by weight:

[0017]

[0018]

[0019] The magnesium zirconium sand particles contain MgO≥80.0wt%, and ZrO2 is 7.0wt% to 16.0wt%;

[0020] The semi-stable zirconium oxide fine powder contains ZrO2+HfO2≥94wt%, and MgO+CaO+Y2O3 is 2wt% to 4wt%;

[0021] The raw material composition does not contain an aluminum spinel component and does not directly introduce an Al2O3 component;

[0022] In the high-performance magnesium-zirconium-carbon skateboard brick, the MgO content is ≥72wt%, the ZrO2 content is ≥4.5wt%, the Al2O3 content is <9wt% (preferably ≤8.7wt%), and the total carbon (TC) content is >7wt% (preferably ≥7.2wt%).

[0023] Calcium-treated steel and other varieties of steel are one of the main application scenarios of the high-performance magnesium-zirconium-carbon skateboard brick of the present invention. As introduced in the background technology of the present invention, the high content of Al2O3 in the skateboard bricks of the prior art is not conducive to the application of these skateboard bricks in calcium-treated steel and other varieties of steel, because the corrosion of calcium on Al2O3 will cause the skateboard bricks with high Al2O3 content to fail quickly. To this end, the present invention particularly proposes a high-performance magnesium-zirconium-carbon skateboard brick with low Al2O3 content, which is particularly suitable for calcium-treated steel and other varieties of steel. The raw material composition of the high-performance magnesium-zirconium-carbon skateboard brick of the present invention does not contain aluminum spinel components, does not involve spinel raw materials, and does not directly introduce Al2O3 components, but uses reduced metal Al powder, Al-Si alloy powder, and Al-Mg alloy powder as Al sources to introduce into the raw material composition. The Al2O3 content in the high-performance magnesium-zirconium-carbon skateboard brick finally obtained is <10wt%, and further ≤8.7wt%. This low Al2O3 content high-performance magnesium-zirconium-carbon skateboard brick can be used for calcium-treated steel and other varieties of steel for a long time, and has excellent corrosion resistance.

[0024] In addition, in order to ensure the application effect in calcium-treated steel and other steel varieties, the high-performance magnesium zirconium carbon slide brick of the present invention also uses semi-stable zirconium oxide fine powder and magnesium zirconium sand particles with a ZrO2 content of 7.0wt% to 16.0wt%, so that the high-performance magnesium zirconium carbon slide brick contains a higher ZrO2 content (≥4.5wt%), reducing the expansion coefficient of the high-performance magnesium zirconium carbon slide brick and improving the corrosion resistance. Other zirconium sources may have corrosion resistance that needs to be further improved (such as zirconium mullite, etc.), or may introduce additional Al2O3 components (such as zirconium corundum).

[0025] Another major feature of the high-performance magnesium-zirconium-carbon skateboard brick of the present invention is that the total carbon content is high (>7wt%, further ≥7.2wt%) and the source is abundant. The total carbon component in the high-performance magnesium-zirconium-carbon skateboard brick is formed by a variety of carbon sources (SiC powder, graphite powder, carbon black, high-temperature asphalt powder, B4C powder, etc.), which makes the high-performance magnesium-zirconium-carbon skateboard brick have high thermal conductivity and thermal shock resistance.

[0026] Several optional methods are also provided below, but they are not intended to be additional limitations on the above-mentioned overall solution, but are merely further supplements or preferences. Under the premise that there are no technical or logical contradictions, each optional method can be combined with the above-mentioned overall solution separately, and multiple optional methods can also be combined.

[0027] In some embodiments, the sum of the weight parts of the high-performance magnesium zirconium carbon skateboard brick, magnesium sand particles, magnesium sand fine powder, magnesium zirconium sand particles, semi-stable zirconium oxide fine powder, metal Al powder, elemental Si powder, Al-Si alloy powder, Al-Mg alloy powder, SiC powder, graphite powder, carbon black, high temperature asphalt powder, and B4C powder is 100 parts.

[0028] In the raw material composition of the high-performance magnesium zirconium carbon skateboard brick of the present invention, Al-Mg alloy powder and Al-Si alloy powder can be used simultaneously, or only one of them can be used. If there are no corresponding conditions, neither of them can be used. When only one of Al-Mg alloy powder and Al-Si alloy powder is used, Al-Mg alloy powder is preferably used, so that the matrix part of the skateboard is more likely to generate reinforcing phases such as β-SiC whiskers, AlN whiskers, flaky Al2OC, MgAl2O4, etc. during the heat treatment process or the use of the skateboard; the volume stability, high temperature mechanical strength, oxidation resistance and slag resistance of the material are improved.

[0029] In the raw material composition of the high-performance magnesium-zirconium-carbon slide brick of the present invention, SiC powder not only serves as a carbon source, but also plays an antioxidant role, reduces the expansion rate of the high-performance magnesium-zirconium-carbon slide brick, and improves the thermal shock resistance.

[0030] The magnesia particles can be at least one of fused magnesia (including large crystalline magnesia) and sintered magnesia.

[0031] In some embodiments, the MgO in the magnesia particles is ≥ 96.0 wt %.

[0032] The magnesia fine powder can be at least one of fused magnesia (including large crystalline magnesia) and sintered magnesia.

[0033] In some embodiments, the MgO in the magnesia fine powder is ≥ 96.0 wt %.

[0034] In some embodiments, the particle size distribution of the magnesia particles is as follows, in parts by weight:

[0035] 2-1 mm 10-25 parts, preferably 15-25 parts,

[0036] 0.999~0.5mm 10~20 pieces,

[0037] 0.499-0.075 mm 10-30 parts, preferably 15-30 parts.

[0038] In some embodiments, the particle size of the magnesia fine powder is less than 0.074 mm.

[0039] The magnesia zircon sand particles may be at least one of fused magnesia zircon sand and sintered magnesia zircon sand.

[0040] In some embodiments, the particle size distribution of the magnesium zircon sand particles is as follows, in parts by weight:

[0041] 2~1mm 0~10 copies;

[0042] 0.999-0 mm 0-30 parts, preferably 0-20 parts, for example 10 parts.

[0043] In some embodiments, the particle size of the semi-stable zirconium oxide fine powder is less than 0.1 mm.

[0044] In some embodiments, the metal Al powder contains Al>97.0wt%.

[0045] In some embodiments, the particle size of the metal Al powder is less than 0.074 mm.

[0046] In some embodiments, the Si content of the elemental Si powder is >97.0 wt %.

[0047] In some embodiments, the particle size of the elemental Si powder is less than 0.074 mm.

[0048] In some embodiments, the Si content in the Al-Si alloy powder is 10wt% to 30wt%, and Si+Al>98wt%.

[0049] In some embodiments, the particle size of the Al-Si alloy powder is less than 0.074 mm.

[0050] In some embodiments, the Al-Mg alloy powder contains Mg>45wt%, and Mg+Al>98wt%.

[0051] In some embodiments, the particle size of the Al-Mg alloy powder is less than 0.074 mm.

[0052] In some embodiments, the particle size of the SiC powder is less than 0.1 mm.

[0053] The graphite powder may be flake graphite.

[0054] In some embodiments, the carbon content of the graphite powder is >94.0 wt %.

[0055] In some embodiments, the particle size of the graphite powder is less than 0.1 mm.

[0056] The carbon black may be nano carbon black.

[0057] In some embodiments, the particle size of the carbon black is 20 to 30 nanometers.

[0058] In some embodiments, the carbon black has C>97.0wt%.

[0059] In some preferred examples, the high temperature asphalt powder has the following indicators: softening point of 150-250°C, coking value of 550°C>75wt%, particle size<0.1mm. The high temperature asphalt powder with the above indicators is more conducive to reducing the expansion rate of high performance magnesium zirconium carbon skateboard bricks.

[0060] In some embodiments, in the B4C powder, B>75wt%, C>17wt%, and B+C>95wt%.

[0061] In some embodiments, the particle size of the B4C powder is <0.045 mm.

[0062] The binder may be a combination of a thermoplastic resin and a curing agent or a thermosetting phenolic resin.

[0063] In some embodiments, the curing agent includes hexamethylenetetramine, etc., and the particle size of the hexamethylenetetramine may be 1 to 0 mm.

[0064] The high-performance magnesium zirconium carbon skateboard brick has a compressive strength of ≥150MPa and a flexural strength of ≥30MPa after drying at 110°C×24h, a high-temperature flexural strength of ≥30MPa at 1400°C×0.5h, a strength retention rate of ≥55% after three times of 1100°C water cooling, and a thermal expansion rate of ≤1.58% at 1500°C.

[0065] [2] The method for preparing the high-performance magnesium zirconium carbon slide brick according to [1] comprises:

[0066] Mixing other raw materials except magnesia sand particles, magnesia zirconium sand particles and binder to obtain premixed powder;

[0067] The magnesia sand particles and the magnesia zirconium sand particles are mixed and ground, and then a binder is added and ground, and then a premixed powder is added and ground, and the obtained mud is trapped and then pressed into shape by a machine, and the formed skateboard brick is baked at 180-220°C and then reduced and fired at 700-1000°C, preferably 750-900°C (for example, 800°C), impregnated with asphalt, and dry distilled at 500-600°C (to remove the volatile matter of the impregnated asphalt) to obtain the high-performance magnesia zirconium carbon skateboard brick. After the dry distillation treatment, the processes of covering steel strips and steel shells, drilling, grinding and coating can also be carried out to obtain the high-performance magnesia zirconium carbon skateboard brick.

[0068] In some embodiments, the trapping time may be 2 to 24 hours.

[0069] In some embodiments, the baking time is not less than 20 hours.

[0070] In some embodiments, the total heating and heat preservation time of the sintering is no less than 24 hours.

[0071] [3] Application of high performance magnesium zirconium carbon slide bricks according to [1] in calcium treated steel.

[0072] Traditional magnesium skateboards are sintered at high temperatures, and then processed through an oil-immersion distillation process to achieve finished products; they have a high thermal expansion rate and are prone to cracking, so their service life is limited; this material is rarely used to make skateboards in China.

[0073] Traditional magnesium-carbon skateboards are also prone to cracking during use due to their high thermal expansion coefficient, and their service life on ladles does not exceed 3 times; this material is not widely used to make skateboards in China.

[0074] Compared with the prior art, the present invention has the following beneficial effects:

[0075] 1. The present invention uses magnesia as the main raw material, which greatly improves the corrosion resistance of the slide plate, especially when used on calcium-treated steel, high-oxygen steel, high-manganese steel and other steel varieties.

[0076] 2. Adding magnesium zirconium sand and semi-stable zirconium oxide to the skateboard, and introducing metal Al powder, elemental Si powder, Al-Si total powder, Al-Mg alloy powder, SiC fine powder, graphite powder, carbon black and high-temperature asphalt powder, etc., has the following advantages:

[0077] a) Adding low expansion materials such as magnesium zircon sand, semi-stable zirconium oxide, SiC and carbon raw materials effectively reduces the thermal expansion rate of the skateboard, improves the thermal conductivity of the skateboard, and greatly improves the thermal shock resistance of the skateboard; the cracks of the skateboard are reduced and the service life is increased.

[0078] b) Introducing Si powder, Al powder, Mg-Al alloy powder and Al-Si alloy powder into the skateboard not only greatly improves the oxidation resistance, but also improves the density and high temperature strength of the skateboard, greatly improving the anti-scouring performance of the skateboard.

[0079] 3. By introducing asphalt powder with high residual carbon rate into the skateboard, the asphalt melts and flows around the aggregate during the baking and medium-low temperature sintering of the skateboard, and is evenly distributed inside the material matrix to form a network structure. During the high-temperature use of the skateboard, the asphalt is cracked to form a network-like graphitized structure, which improves the retention rate of the material's flexural strength and improves its thermal shock resistance.

[0080] In summary, the prepared magnesium zirconium carbon skateboard bricks have high corrosion resistance. Through medium and low temperature heat treatment, the skateboard has sufficient strength. At the same time, it can be self-sintered again during use, thereby greatly improving the medium and high temperature strength of the material. At the same time, the material also has very excellent corrosion resistance, oxidation resistance, thermal shock stability, wear resistance, toughness, etc., thus solving the problems of erosion, cracking, thermal spalling, oxidation roughening and falling off around the casting hole that are prone to occur during the use of the skateboard on the grade steel. DETAILED DESCRIPTION

[0081] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples where no specific conditions are indicated are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0082] The raw material composition of the skateboard bricks of each embodiment and comparative example is shown in Table 1 (unit: weight part). The raw materials involved are described as follows:

[0083] MgO in magnesia ≥ 96.0wt%;

[0084] MgO ≥ 80.0wt% and ZrO2 7.0wt% to 16.0wt% in magnesium zircon sand;

[0085] Fused spinel, MgO accounts for 25wt% to 30wt%, MgO + Al2O3 ≥ 97wt%;

[0086] In semi-stable zirconia, ZrO2+HfO2≥94wt%, MgO+CaO+Y2O3 is 2wt%~4wt%;

[0087] Al>97.0wt% in metal Al powder;

[0088] Mg>45wt%, Mg+Al>98wt% in Al-Mg alloy powder;

[0089] Si>97.0wt% in elemental Si powder;

[0090] Si in Al-Si alloy powder is 10wt% to 30wt%, Si+Al>98wt%;

[0091] The carbon content in flake graphite is >94.0wt%;

[0092] C>97.0wt% in nano carbon black;

[0093] In B4C powder, B>75wt%, C>17wt%, B+C>95wt%;

[0094] The indicators of high-temperature asphalt powder are as follows: softening point is 150-250℃, and coking value at 550℃ is >75wt%.

[0095] Table 1

[0096]

[0097] The method for preparing the skateboard bricks of each embodiment and comparative example includes:

[0098] First, the raw materials other than magnesia sand particles, magnesia zirconium sand particles and binder are pre-mixed and uniformly prepared into premixed powder; then the granular aggregate is put into a high-speed mixer and mixed for 3-5 minutes, and then the binder is added and mixed for 5-8 minutes, and finally the premixed powder is added and mixed for 30-50 minutes. The mixed mud is trapped for 2-24 hours, and then pressed and formed on a 1000t electric programmable press. The formed skateboard bricks enter the drying kiln and are baked at 180-220℃ for more than 20 hours. The baked skateboard bricks are then reduced and fired at 800℃ (the total heating and insulation time is more than 24 hours), asphalt impregnated, and distilled at 500℃, and then covered with steel strips and steel shells, drilled, ground and coated to obtain skateboard bricks.

[0099] Table 2 shows the performance test results of the skateboard bricks of various embodiments and comparative examples.

[0100] Table 2

[0101]

[0102] It can be seen from Table 2 that the high-performance magnesium zirconium carbon skateboard prepared by the present invention has significantly improved compressive strength and flexural strength, high-temperature flexural strength, and flexural strength retention rate at room temperature and after medium and high temperature treatment; the thermal expansion rate is effectively reduced, and the thermal shock resistance is significantly improved. The high-performance magnesium zirconium carbon skateboard prepared by the present invention can be self-sintered during use, which will greatly improve the medium and high temperature strength of the material, so that the material has very excellent antioxidant properties, thermal shock stability, wear resistance, toughness, etc., thereby solving the problems of cracks, thermal peeling, oxidation roughening, and block falling around the casting hole that are easy to occur during the use of the skateboard, and can greatly improve the service life.

[0103] The high-performance magnesium zirconium carbon skateboard brick prepared by the present invention has the characteristics of high density, low thermal expansion rate, high high temperature strength, high strength retention rate, etc.; it has high corrosion resistance, thermal shock resistance, scouring resistance, and oxidation resistance when casting calcium-treated steel, high manganese steel, high oxygen steel and other steel varieties. When used on medium and large ladles, its service life reaches more than 4 times; when used on medium ladles, it can be used for more than 6 furnaces in a row. The skateboard made of this material can also be used for casting ordinary steel, and the skateboard has strong applicability.

[0104] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A high-performance magnesium zirconium carbon slide brick suitable for calcium treated steel, characterized in that: In parts by weight, the raw material composition includes: The magnesium zirconium sand particles contain MgO≥80.0wt% and ZrO2 is 7.0wt% to 16.0wt%; The semi-stable zirconium oxide fine powder contains ZrO2+HfO2≥94wt%, and MgO+CaO+Y2O3 is 2wt% to 4wt%; The raw material composition does not contain an aluminum spinel component and does not directly introduce an Al2O3 component; In the high-performance magnesium-zirconium-carbon skateboard brick, the MgO content is ≥72wt%, the ZrO2 content is ≥4.5wt%, the Al2O3 content is <9wt% (preferably ≤8.7wt%), and the total carbon content is >7wt% (preferably ≥7.2wt%).

2. The high performance magnesium zirconium carbon slide brick according to claim 1 is characterized in that: The sum of the weight parts of magnesia sand particles, magnesia sand fine powder, magnesia zirconium sand particles, semi-stable zirconia fine powder, metal Al powder, elemental Si powder, Al-Si alloy powder, Al-Mg alloy powder, SiC powder, graphite powder, carbon black, high-temperature asphalt powder, and B4C powder is 100 parts.

3. The high performance magnesium zirconium carbon slide brick according to claim 1 is characterized in that: The magnesia particles are at least one of fused magnesia and sintered magnesia, and the MgO in the magnesia particles is ≥ 96.0wt%; The magnesia fine powder is at least one of fused magnesia and sintered magnesia, and the MgO in the magnesia fine powder is ≥96.0wt%; In parts by weight, the particle size distribution of the magnesia particles is: 2-1 mm 10-25 parts, preferably 15-25 parts, 0.999~0.5mm 10~20 pieces, 0.499-0.075 mm 10-30 parts, preferably 15-30 parts; The particle size of the magnesia fine powder is less than 0.074 mm.

4. The high performance magnesium zirconium carbon slide brick according to claim 1, characterized in that: The magnesia zircon sand particles are at least one of fused magnesia zircon sand and sintered magnesia zircon sand; In parts by weight, the particle size distribution of the magnesia zirconium sand particles is: 2~1mm 0~10 copies; 0.999~0mm 0~30 parts, preferably 0~20 parts.

5. The high performance magnesium zirconium carbon slide brick according to claim 1, characterized in that: The particle size of the semi-stable zirconium oxide fine powder is less than 0.1 mm; The Al content of the metal Al powder is greater than 97.0 wt %, and the particle size of the metal Al powder is less than 0.074 mm; The Si in the elemental Si powder is greater than 97.0wt%, and the particle size of the elemental Si powder is less than 0.074mm; The Al-Si alloy powder contains 10wt% to 30wt% Si, Si+Al>98wt%, and the particle size of the Al-Si alloy powder is less than 0.074mm; The Al-Mg alloy powder contains Mg>45wt%, Mg+Al>98wt%, and the particle size of the Al-Mg alloy powder is less than 0.074mm.

6. The high performance magnesium zirconium carbon slide brick according to claim 1, characterized in that: The particle size of the SiC powder is less than 0.1 mm; The graphite powder is flake graphite, the carbon content of the graphite powder is greater than 94.0wt%, and the particle size of the graphite powder is less than 0.1mm; The carbon black is nano carbon black, the particle size of the carbon black is 20 to 30 nanometers, and C>97.0wt% in the carbon black; The indicators of the high temperature asphalt powder are as follows: softening point is 150-250°C, coking value at 550°C>75wt%, particle size<0.1mm; In the B4C powder, B>75wt%, C>17wt%, B+C>95wt%, and the particle size of the B4C powder is <0.045mm.

7. The high performance magnesium zirconium carbon slide brick according to claim 1, characterized in that: The binder is a combination of a thermoplastic resin and a curing agent or a thermosetting phenolic resin; The curing agent includes hexamethylenetetramine; the particle size of the hexamethylenetetramine is 1 to 0 mm.

8. The high performance magnesium zirconium carbon slide brick according to any one of claims 1 to 7, characterized in that: The high-performance magnesium zirconium carbon skateboard brick has a compressive strength of ≥150MPa and a flexural strength of ≥30MPa after drying at 110°C×24h, a high-temperature flexural strength of ≥30MPa at 1400°C×0.5h, a strength retention rate of ≥55% after three times of 1100°C water cooling, and a thermal expansion rate of ≤1.58% at 1500°C.

9. The method for preparing high-performance magnesium zirconium carbon slide brick according to any one of claims 1 to 8, characterized in that: include: Mixing other raw materials except magnesia sand particles, magnesia zirconium sand particles and binder to obtain premixed powder; The magnesia sand particles and the magnesia zirconium sand particles are mixed and ground, and then a binder is added and ground, and then a premixed powder is added and ground. The obtained mud is trapped and then pressed into shape by a machine. The formed skateboard bricks are baked at 180-220°C and then reduced and calcined at 700-1000°C, preferably 750-900°C, impregnated with asphalt, and dry distilled at 500-600°C to obtain the high-performance magnesia zirconium carbon skateboard bricks.

10. Use of the high performance magnesium zirconium carbon slide brick according to any one of claims 1 to 8 in calcium treated steel.

Citation Information

Patent Citations

  • Air brick for magnesia carbon ladle and method for producing the same

    CN101391897A

  • Preparation method and proportion of components of low-carbon magnesium-calcium carbon brick for manufacturing inner lining of steel-making refining furnace

    CN102040389A

  • Method for preparing magnesium-zirconium-carbon slide gate nozzle

    CN102584293A

  • Magnesium-zirconium ring of slide plate for calcium-treated steel and preparation method thereof

    CN102643099A

  • Aluminium titanate-zirconia composite slide plate and preparation method thereof

    CN102898150A